MoneyWatch Report - Green, Anne-Marie; Kaul, Shanelle (CBS Morning News, 2019)
The family that owns the company that makes OxyContin is calling a Massachusetts' lawsuit false and misleading. This is the Sackler family's first court response to allegations that individual family members helped fuel the deadly opioid epidemic. Attorneys for the Sackler family say the claims must be dismissed. Massachusetts was among the first state government to sue the family as well as the company last year.